Combined administration of mesenchymal stem cells overexpressing IGF-1 and HGF enhances neovascularization but moderately improves cardiac regeneration in a porcine model. Issue 1 (December 2016) - Gómez-Mauricio, Guadalupe; Moscoso, Isabel; Martín-Cancho, María-Fernanda; Crisóstomo, Verónica; Prat-Vidal, Cristina; Báez-Díaz, Claudia; Sánchez-Margallo, Francisco; Bernad, Antonio
Abstract Background Insulin-like growth factor 1 (IGF-1) and hepatocyte growth factor (HGF) are among the most promising growth factors for promoting cardiorepair. Here, we evaluated the combination of cell- and gene-based therapy using mesenchymal stem cells (MSC) genetically modified to overexpress IGF-1 or HGF to treat acute myocardial infarction (AMI) in a porcine model. Methods Pig MSC from adipose tissue (paMSC) were genetically modified for evaluation of different therapeutic strategies to improve AMI treatment. Three groups of infarcted Large White pigs were compared (I, control, non-transplanted; II, transplanted with paMSC-GFP (green fluorescent protein); III, transplanted with paMSC-IGF-1/HGF). Cardiac function was evaluated non-invasively using magnetic resonance imaging (MRI) for 1 month. After euthanasia and sampling of the animal, infarcted areas were studied by histology and immunohistochemistry. Results Intramyocardial transplant in a porcine infarct model demonstrated the safety of paMSC in short-term treatments. Treatment with paMSC-IGF-1/HGF (1:1) compared with the other groups showed a clear reduction in inflammation in some sections analyzed and promoted angiogenic processes in ischemic tissue. Although cardiac function parameters were not significantly improved, cell retention and IGF-1 overexpression was confirmed within the myocardium. Conclusions The simultaneous administration of IGF-1- and HGF-overexpressing paMSC appears not to promote a synergistic effect or effective repair. The combined enhancement of neovascularization and fibrosis in paMSC-IGF-1/HGF-treated animals nonetheless suggests that sustained exposure to high IGF-1 + HGF levels promotes beneficial as well as deleterious effects that do not improve overall cardiac regeneration.